Altered Global Synchronizations in Patients With Parkinson’s Disease: A Resting-State fMRI Study - Li, Mengyan; Liu, Yanjun; Chen, Haobo; Hu, Guihe; Yu, Shaode; Ruan, Xiuhang; Luo, Zhenhang; Wei, Xinhua; Xie, Yaoqin (Frontiers in Aging Neuroscience, 2019)
Background: Abnormalities of cognitive and movement functions are widely reported in Parkinson’s disease (PD). The mechanisms therein are complicated and assumed to a coordination of various brain regions. This study explored the alterations of global synchronizations of brain activities and investigated the neural correlations of cognitive and movement function in PD patients. Methods: Age-match of 35 patients with PD and 35 normal controls (NC) were enrolled in resting-state functional magnetic resonance imaging (fMRI) scanning. Degree centrality (DC) were calculated to measure the global synchronizations of brain activity for two groups. Neural correlations between DC and cognitive function (Frontal Assessment Battery, FAB) as well as movement function (Unified Parkinson’s Disease Rating Scale, UPDRS-III) were examined across the whole brain within Anatomical Automatic Labeling (AAL) templates. Results: In PD group, increased DC was observed in left fusiform gyrus extending to inferior temporal gyrus, left middle temporal gyrus and angular gyrus, while it was decreased in right inferior opercular-frontal gyrus extending to superior temporal gyrus. The DC in significant region of fusiform gyrus was positively correlated with UPDRS-III scores in PD (r = 0.41, p = 0.0145). Higher FAB scores were shown in NC than PD (p < 0.0001). Correlative analysis of PD between DC and FAB showed negative results (p < 0.05) in frontal cortex, whereas positive in insula and cerebellum. As for the correlations between DC and UPDRS-III, negative correlation (p < 0.05) was observed in bilateral inferior parietal lobule and right cerebellum, whereas positive correlation (p < 0.05) in bilateral hippocampus and para-hippocampus gyrus (p < 0.01). Conclusion: The altered global synchronizations revealed altered cognitive and movement functions in PD. The findings suggested that the global functional connectivity in fusiform gyrus, cerebellum and hippocampus gyrus are critical regions in the identification of cognitive and movement functions in PD. This study provides new insights on the interactions among global coordination of brain activity, cognitive and movement functions in PD.